2024
DOI: 10.1039/d4cs00097h
|View full text |Cite
|
Sign up to set email alerts
|

Low oxidation state and hydrido group 2 complexes: synthesis and applications in the activation of gaseous substrates

Matthew J. Evans,
Cameron Jones

Abstract: This review summarises advances in the chemistry of low-oxidation state and hydrido group 2 metal complexes, focussing on their use for the reductive activation of feed-stock gaseous small molecules, and their subsequent transformation into value added products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 238 publications
(518 reference statements)
0
0
0
Order By: Relevance
“… 1 Lithium, the lightest alkali metal, has been at the forefront of AMM, though both sodium and potassium have also made significant contributions to AMM down the years. Recently, an emerging focus on molecular main group hydrides, 2 and s-block hydrides in particular, has broadened the scope of AMM to include the much rarer studied heavier alkali metals rubidium and cesium. 3 Moreover, these heavier alkali metals are also finding application in unlikely AMM reactions such as the reduction of lithium cations to lithium metal.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Lithium, the lightest alkali metal, has been at the forefront of AMM, though both sodium and potassium have also made significant contributions to AMM down the years. Recently, an emerging focus on molecular main group hydrides, 2 and s-block hydrides in particular, has broadened the scope of AMM to include the much rarer studied heavier alkali metals rubidium and cesium. 3 Moreover, these heavier alkali metals are also finding application in unlikely AMM reactions such as the reduction of lithium cations to lithium metal.…”
Section: Introductionmentioning
confidence: 99%
“…In 2004, Carmona et al isolated the first Zn–Zn bonded complex Cp* 2 Zn 2 (Cp* = C 5 Me 5 ) with a zinc formal oxidation state of +1, which was formed most probably by the coupling of two [Cp*Zn·] radicals . Ever since this landmark discovery, the synthesis and structural studies of Zn–Zn bonded compounds showed significant progress. , In contrast, their reactivity was much less explored when compared with that of the Mg–Mg bonded counterparts. It is well-established that light irradiation of homonuclear metal–metal bonded compounds may result in the formation of corresponding metal-centered radicals through a homolytic cleavage reaction . As part of our continued interest in organozinc chemistry, we decided to probe the reactivity of the dizinc­(I) complex via a photoactivation strategy.…”
Section: Introductionmentioning
confidence: 99%
“…< + 2) has gathered pace since Jones and co-workers’ 2007 report of isolable Mg( i ) species. 1 While the kinetic stability of, for example, compounds I and II (Fig. 1), 2 was ensured by the use of bulky β-diketiminate (BDI Ar ) spectator anions, the thermochemical viability of their synthesis was in intuitive accord with the standard reduction potentials ( E 0 , V) of the potassium (K + (aq) + e − K (s) → −2.92 V) and magnesium( ii ) (Mg 2+ (aq) + 2e − → Mg (s) −2.36 V) starting materials.…”
mentioning
confidence: 99%
“…3,4 Consistent with this supposition, similar alkali metal reduction has since realised a substantial variety of related Mg( i ) derivatives. 1,5–16…”
mentioning
confidence: 99%